EXPERIENCE WITH IN ON-X PROSTHESIS IN HEART VALVE REPLACEMENT - M. A. Sazonenkov; D. A. Basarab; S. S. Krivorot; M. N. Korneluk (Вестник трансплантологии и искусственных органов)
The prosthesis ON-X carcas has advantages in implantation commodity and safety, effective orifice area. We pe- sent results of this prosthesis usage during perioud of 2006–2009 years. This time 792 operations with AC were completed. In mitral position were implanted 132 (91,7%) prostheses ON-X. Of them 80 (60,6%) valves were sutured with complete or partial preservation of posterior leaflet and 26 (19,7%) valves – with total MV preser- vation. In aortic position we implanted 76 (53,9%) valves ON-X. Only 3 cases needed posterior aortoplasty for the N 23 prosthesis implantation. In perioperative and late postoperative periods we didn’t meet prostheses thrombosis or dysfunction. Reoperati- ons for high prosthesis gradients didn’t occur in postoperative period. Late postoperatively there were 3 (1,1%) cases of embolic events related to the incorrect anticoagulant treatment.